PREFERENSI WISATAWAN MILENIAL NUSANTARA PADA DAYA TARIK WISATA SWAFOTO DI BALI - Putu Devi Rosalina; Luh Eka Susanti; Made Widya Paramitha (Jurnal Ilmiah Hospitality Management, 2019)
ABSTRACT Millennial tourists regards traveling not just about enjoying nature and culture, or strolling around, instead millennials assume that traveling is when immersed in an interesting experience. The purpose of this study is to find out how the preferences of domestik millennial tourists visiting Selfie Tourist Attraction (STA) in Bali, as well as what tourist activities need to be developed. The approach in this research is qualitative, referring to McIntosh's Motivation theory and Leiper's Tourist Attraction Theory. The locus of research is in five STAs including: Twin Hill in Gianyar Regency, Big Garden Corner in Denpasar City, Tukad Badung in Denpasar City, Merta Sari Sanur Beach and Selfie Wanagiri Tourism in Buleleng Regency . Data will be collected through interview and the distribution of 50 questionnaires with accidental sampling. The results revealed that the majority of tourists' motivation to visit is driven by the desire to escape or so-called Fantasy Motivation by 50%, while physical motivation is by 26%, social by 20%, and culture merely by 4%. Furthermore, regarding its preference analysis, domestic millenial tourists are very supportive for the government's performance and enthusiastic for the success of the stakeholders in developing and advancing STA, as seen from the percentage of 94% of tourists choosing to visit by considering the success of the stakeholders in managing STA. In addition, there are a number of tourism activities that need to be developed to optimize the potential of STA, such as: holding cultural events on a regular basis, adding playgrounds for children, adding spots for selfies, and renovating selfie photo spots that are already inadequate. Tourists also argued the need to maintain cleanliness and the addition of public facilities.